Pattern of Specific Dermatoses During Pregnancy - Afroz, Rozina; Chowdhury, Shahabuddin Ahmed; Mannan, MA; Talukdar, Sudarshan Kumar (Medicine Today, 2015)
Dermatoses unique to pregnancy are rare but important to recognize because they may be intensely pruritic or painful to the mother and they may pose significant risk to the patient, her fetus or both. Dermatoses of pregnancy usually does not get attention. Both the obstetrician and the patient are more focused on the pregnancy itself. Some dermatoses of pregnancy elevate the risk of adverse fetal events, it is critical to distinguish them from underlying skin conditions that simply present or flare during pregnancy. Early diagnosis and treatment may help to reduce morbidity and mortality to the gravid patient and her fetus and minimize fetal exposure to unnecessary treatments. This clinical study shows, about 8% pregnant women had specific dermatoses. Maximum 40 (41.6%) patients were in between the age of 25 to 29 years. According to trimester, 60 (62.5%) patients were in 3rd trimester. In case of gravida, maximum 59 (61.5%) patients were primigravida. In this study, pruritic urticarial papules and plaques of pregnancy ( PUPPP ) was the most common dermatoses during pregnancy. Medicine Today 2015 Vol.27(1): 20-22